Exposição a vibrações ocupacionais de mãos e braços no uso de equipamentos mecânicos portáteis na cultura do cafeeiro - OLIVEIRA JUNIOR, G. G. (2019)
Coffee is one of the most important agricultural crops in the country and over time has been undergoing significant changes, especially regarding the mechanization and semi-mechanization process of handling. In the Southern of Minas Gerais, the use of portable mechanical equipment for mowing and harvesting coffee crop has intensified. The use of this equipment may expose occupationally workers to localized vibrations by transferring the mechanical vibrations from the tool to the operator’s hands and arms. Given the above, this study aimed to quantify the levels of hands and arms vibration that brushcutters and trimmers operators are exposed in coffee crop. This study was developed at the Federal Institute of Education, Science and Technology of Southern Minas Gerais (IFSULDEMINAS), Campus Muzambinho - MG. Multifunctional equipment called brushcutters and trimmers machines were evaluated under usual and routine working conditions in the coffee crop. Data acquisition was performed using the SV 103, Svantek vibration meter with triaxial (“x”, “y” and “z”) transducers (accelerometers) installed directly on each worker’s hands at the tool contact point. The collected data were processed in Svantec Supervisor 1.12 software. Results showed that for all conditions of the present study the action level of 2.5 ms-2 was exceeded. The resulting acceleration of the brushcutter equipment with Dual Grip handlebar (DGH) was 37.45% on average lower than the equipment operation with circular cable (CC). The highest vibration levels were quantified during the operation of the trimmer equipment, exceeding the exposure limit of 5 ms-2 for all conditions evaluated, which is the limit allowed for an 8-hour working day according to the standards. (Regulatory Standard - NR 15 and Occupational Hygiene Standard - NHO 10) and the criteria of the American Conference of Governmental Industrial Hygienists (ACGIH).